2015
DOI: 10.3389/fevo.2014.00087
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem services—current challenges and opportunities for ecological research

Abstract: † These authors have contributed equally to this work.The concept of ecosystem services was originally developed to illustrate the benefits that natural ecosystems generate for society and to raise awareness for biodiversity and ecosystem conservation. In this article we identify major challenges and opportunities for ecologists involved in empirical or modeling ecosystem service research. The first challenge arises from the fact that the ecosystem service concept has not been generated in the context of manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
100
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 125 publications
0
100
0
3
Order By: Relevance
“…Because of competition for land and natural resources, increasing the supply of one ecosystem service (ES) may result in reducing the supply of others (Minang et al, 2014;Seppelt et al, 2014;. Reconciling multiple conflicting objectives of ecosystem management and dealing with ES tradeoffs are major challenges of sustainable development and sustainability science (Birkhofer et al, 2015;Carpenter et al, 2009;Grêt-Regamey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of competition for land and natural resources, increasing the supply of one ecosystem service (ES) may result in reducing the supply of others (Minang et al, 2014;Seppelt et al, 2014;. Reconciling multiple conflicting objectives of ecosystem management and dealing with ES tradeoffs are major challenges of sustainable development and sustainability science (Birkhofer et al, 2015;Carpenter et al, 2009;Grêt-Regamey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…the focus of our study) has received much more attention than other dimensions of tradeoffs (Turkelboom et al, 2017). It has been conflated in an inconsistent and misleading way to the concepts of "ES relationships", "ES interactions" and "ES associations" in literature (Birkhofer et al, 2015;Mouchet et al, 2014;Seppelt et al, 2011). Mouchet et al (2014) observed that the word "tradeoff" should not be used to describe static negative associations between ES (like spatial congruence, spatial concordance, co-occurrence or overlap of ES), but reserved for associations repeated in time and space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding ES interactions at different temporal scales, both short-term and long-term, is another key challenge (Mouchet et al 2014, Birkhofer et al 2015. Ecosystem service interactions may involve time lags whereby historical decisions influence current provisioning of ES (Dallimer et al 2015).…”
Section: Introductionmentioning
confidence: 99%